ANALISIS PERILAKU EFEK RETROFIT KOLOM BETON BERKOMPOSISI STEEL FIBER (ENGINEERED CEMENTITIOUS COMPOSITE / ECC) AKIBAT BEBAN AKSIAL DENGAN MENGGUNAKAN SOFTWARE BERBASIS FINITE ELEMENT ANALYSIS - Bagas Rahmandita Subchan; Gati Annisa Hayu; Entin Hidayah (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
This study presents a simulation analysis of the non-linear behavior of retrofit concrete material due to uniaxial loads modeled in the form of cylinders measuring 150 mm in diameter and 200 mm in depth using the ABAQUS. Analysis of this auxiliary program includes cases of normal concrete retrofit, concrete with retrofit concrete with a composition of 1% steel fiber, and concrete with retrofit concrete composed of 2% steel fiber. From the results of the study conducted, it was shown that in modeling the properties of concrete damaged plasticity in ABAQUS, the use of accurate compressive behavior equations for concrete cases with normal concrete retrofit was core concrete and retrofit concrete using the Alfarah, et al equation. For the case of concrete with steel fiber composition retrofit, core concrete uses the Alfarah equation, and retrofit concrete uses Zhou Jiajia, et al. Whereas to model the tensile behavior accurately in the case of concrete with normal concrete retrofit using the Alfarah, et al equation. And the case of concrete with retrofit steel fiber compositions using the CEB-FIB equation and the Ali & Nehdi equation. The results of ABAQUS analysis of force vs. displacement show a graphical pattern close to the similarity of retrofit concrete column experimental results ECC1 error force ratio and displacement 14.86% and -10.60%, and ECC2 14.82% and 8.01). Based on the stress analysis shows that there is a gradual increase in core concrete where the peak of stress is found in the core area of the concrete core and in the retrofit area is divided into two regions, namely stressing on the center and pulling on a small part of upper and lower column retrofit.